Hubungan Jenis Kelaamin dan Pekerjaan Terhadap Kepatuhan Melaksanakan Protokol Kesehatan 6M Covid-19 Pada Masyarakat Wilayah Kerja Puskesmas Rajabasa Indah Bandar Lampung - Mochammad Aulia Febriansyah; Khoidar Amirus; Dalfian Dalfian (Malahayati Nursing Journal, 2022)
ABSTRACT Coronavirus disease-19 (COVID-19) is a type of acute respiratory disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Community compliance with health protocols is very important to break the chain of the spread of COVID-19. However, based on the survey results, 7 (70%) of 10 (100%) people disobedience in implementing the health protocol 6M COVID-19. To determine the correlation between gender and occupation on compliance with implementing the 6M health protocol in the community working area of the Rajabasa Indah Public Health Center Bandar Lampung in 2021. This type of research is analytic observational with a cross-sectional research design. The study was conducted in February 2021 using a questionnaire. Sampling using accidental sampling technique with a total sample of 214 respondents. Data were analyzed using the Chi Square test. Based on the results of this study, it was found that the most respondents who were obedient in implementing the 6m COVID-19 health protocol were women as many as 69 (62.2%) respondents from a total of 214 (100%) respondents, and from the occupational group, 75 (62.5%) respondents from a total of 214 (100%) respondents. From The Chi-Square test results, it was found that there was a significant relationship between gender (p=0.010) and occupation (p=0.004) to compliance with implementing the 6M COVID – 19 health protocol in the community of the Rajabasa Indah Bandar Lampung Health Center working area 2021. It is recommended for the community, especially to keep the distance between friends while working and keep using masks, then for elderly workers are sought not to work too often outside the home. Keywords: Compliance, Gender, Health Protocol 6M COVID-19, Occupation ABSTRAK Coronavirus disease-19 (COVID-19) merupakan jenis penyakit saluran pernapasan akut yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Kepatuhan masyarakat terhadap protokol Kesehatan sangatlah penting untuk memutus rantai penyebaran COVID-19. Namun berdasarkan hasil presurvei didapatkan 7 (70%) dari 10 (100%) orang tidak patuh dalam melaksanakan protokol kesehatan 6M COVID-19. Tujuan penelitian untuk mengetahui hubungan jenis kelamin dan  pekerjaan terhadap kepatuhan melaksanakan protokol kesehatan  6M pada masyarakat wilayah kerja puskesmas Rajabasa Indah Bandar Lampung tahun 2021. Jenis penelitian ini adalah analitik observasional dengan desain penelitian cross sectional. Penelitian dilakukan pada bulan Februari 2021 dengan menggunakan kuisioner. Pengambilan sampel mengunakan teknik accidental sampling dengan jumlah sampel sebanyak 214 responden . Data dianalisis menggunakan uji Chi Square. Berdasarkan hasil penelitian ini didapatkan bahwa paling banyak responden yang patuh dalam melaksanakan protokol kesehatan 6M COVID-19 yaitu berjenis kelamin perempuan sebanyak 69 (62.2%) responden dari total 214 (100%) responden, dan dari kelompok pekerjaan yaitu sebanyak 75 (62,5%) responden dari total 214  (100%) responden. Dari hasil uji Chi-Square didapatkan bahwa ada hubungan yang signifikan antara jenis kelamin (p=0,010) dan pekerjaan (p=0,004) terhadap kepatuhan melaksanakan protokol kesehatan 6M COVID – 19 pada masyarakat wilayah kerja Puskesmas Rajabasa Indah Bandar Lampung 2021. Disarankan bagi masyarakat, terutama menjaga jarak antar teman disaat bekerja tetap menggunakan masker,lalu untuk pekerja usia lanjut diusahakan untuk tidak terlalu sering bekerja diluar rumah. Kata Kunci: Jenis Kelamin, Pekerjaan, Kepatuhan, Protokol Kesehatan 6M COVID-19